2005
DOI: 10.1038/sj.leu.2404061
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of Toll-like receptor-7 activation on chronic lymphocytic leukemia cells

Abstract: Weak immunogenicity of chronic lymphocytic leukemia (CLL) cells may contribute to disease progression and inhibit effective immunotherapy. Accordingly, agents that enhance the immunogenicity of CLL cells may be useful in immunotherapeutic approaches to this disease. Since Toll-like receptors (TLRs) are major regulators of innate immunity and initiation of adaptive immunity, we studied the effects of viral pathogen associated molecular pattern agonists (that are recognized by TLRs) on the costimulatory phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(104 citation statements)
references
References 24 publications
4
98
0
2
Order By: Relevance
“…It has been suggested that the stimulation of TLRs expressed on B-CLL cells could increase immunogenicity of tumor cells and thus potentially contribute to the induction of leukemia-specific immune response. [15][16][17][18] Several studies also suggested that TLR-9 agonists decrease viability of B-CLL cells and increase susceptibility of B-CLL cells to apoptosis in the cell culture. 19,20 However, a concise study including the analysis of TLRs expression pattern, comparison with normal B cells and functional consequences of TLRs stimulation on B-CLL cells has not yet been performed.…”
mentioning
confidence: 99%
“…It has been suggested that the stimulation of TLRs expressed on B-CLL cells could increase immunogenicity of tumor cells and thus potentially contribute to the induction of leukemia-specific immune response. [15][16][17][18] Several studies also suggested that TLR-9 agonists decrease viability of B-CLL cells and increase susceptibility of B-CLL cells to apoptosis in the cell culture. 19,20 However, a concise study including the analysis of TLRs expression pattern, comparison with normal B cells and functional consequences of TLRs stimulation on B-CLL cells has not yet been performed.…”
mentioning
confidence: 99%
“…However, recent phase I/II trials of CpG oligonucleotides in lymphoma patients provided no evidence of clinical responses despite increased NK activation (Link et al, 2006). Similarly, our recent phase I/II trial of a specific TLR7 agonist (852A; Harrison et al, 2007) in CLL patients has not shown strong clinical activity (manuscript in preparation), in contrast to the striking effects that were noted in vitro (Spaner et al, 2006;Shi et al, 2007).…”
Section: Clinical Results With Tlr Agonists In Hematologic Malignanciesmentioning
confidence: 84%
“…Accordingly, it seems more likely that the therapeutic effects of BCG or Coley's toxins resulted from the direct effects of TLR agonists on tumor cells. Importantly, primary leukemia cells become more sensitive to CTLs after several days of activation by TLR agonists in vitro (Spaner et al, 2006), a finding that may be highly relevant when thinking of using such agents to treat hematologic cancers. The ability of TLR agonists to sensitize leukemia cells to killing by CTLs appears to extend to cytotoxic agents (Shi et al, 2007).…”
Section: Mechanism Of Action Of Tlr Agonists In Cancermentioning
confidence: 99%
See 2 more Smart Citations